Knowledge and attitude regarding legal and ethical aspects in nursing among nurses in a tertiary care teaching hospital, Nepal - Rimal, Himala (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Health care laws and ethics serve as a hallmark in maintaining the equilibrium in the delivery of health care services. The study aimed to find out the knowledge and attitude regarding the legal and ethical aspects of nursing. Method: A cross-sectional study was conducted in Patan Hospital, Patan Academy of Health Sciences, Nepal, from July to August 2017. A self-administered structured questionnaire was used to find out knowledge and attitude regarding legal and ethical aspects in nursing and relation to the demographics- age, an academic qualification in nursing, year of experiences, designation, and place of work in different departments of the hospital. Ethical approval was obtained. Data were analyzed using SPSS, Chi-square test, and the Pearson correlation coefficient was used to determine the association. Result: Findings revealed that among 200 nurses, 26.0% had good knowledge (score >75%), 62.0% average knowledge (score 50%-75%) and 12.0% poor knowledge (score <50%) regarding legal and ethical aspects in nursing. Similarly, 64.5% of nurses had a favourable attitude (score >50%) while 35.5% had an unfavourable attitude on legal and ethical aspects. Knowledge and attitude had no statistically significant association with demographic variables. Conclusion: Most of the nurses had an average level of knowledge and more than half of them had a favourable attitude regarding legal and ethical aspects of nursing.